Training of Reading the Quran and Basic English at TPA Darussalam Bailang Mosque - Andi Mukarrramah Nagauleng; Fadhlan Saini; Nur Halimah; Indah Wardaty Saud; Jihan Fahira Songkaton (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2021)
Problems faced in nowadays Islamic education are the children's low interest in the number of hours of lessons, teachers, facilities, and methods of learning to read and the Qur'an are limited. In Bailang Village, this phenomenon is also happening. From the observation, most of the children are more interested in watching TV than learning to read the Qur'an. Many children and adolescents have not been able to read and write the Qur'an until now. This situation is very alarming; thus proper handling from various parties is necessary to overcome this problem quickly and precisely. This program aims to improve elementary school students' reading the Qur'an ability and mastering basic English language skills for daily communication. This activity was carried out for one week, in August 2020, at the Darussalam mosque, Bailang village, Manado City. The results obtained from the activity are that the ability of elementary school students to read the Qur'an is still relatively lacking, so an appropriate method is needed in teaching reading the Qur'an. The methods that can be used include applying learning methods that are preferred by students so that the ability to absorb lessons can increase. However, after the training done, there was an increase in students' skills in reading the Qur'an and basic English.